Elite female athlete research: stop searching for the `magic P` - Burden, R.; Shill, A.; Bishop, N. (Experimental Physiology, 2021)
In recent years, the call for a priority need for research in female athletes has grown louder (Bruinvels et al., 2017). Practitioners, coaches and athletes are crying out for more informed support. Certainly, there are signs of positive change, with a visible increase in female athlete specific publications. Yet, whilst the gap may be closing, it remains significant in elite populations where studies in elite female athletes remain limited. Studies in truly elite female athletes are often statistically underpowered and therefore not considered publication worthy, as peer-review feedback we and others have experienced has suggested. But isn't that the point? The elite population is a limited number - these are the top 5% performers of their sport - but if academia continues to work with a mindset that elite sport requires an evidence-based practice approach, then more often than not this means meeting the magic `P < 0.05' or alternative statistical approval to be considered of publication value. Yet, by their very nature, elite athletes are elite precisely because they are statistical outliers. The nature of elite sport does not easily lend itself to traditional experimental design; the population is very small, and the characteristics of elite sport environments mean researchers have little room for manoeuvre when it comes to delivering interventions and requesting athlete time commitments. Yet, academia appears steadfast in the belief that change in practice still largely relies on published outcomes, which can only come in the form of a cohort study.